Human Factor of Formal Engineering Methods in Validating Requirement Specification - Fauziah, Zainuddin; Ruzaini, Abdullah Arshah; Rozlina, Mohamed; Rahmah, Mokhtar (American Scientific Publishers, 2017)
The target of the study is to apply the success of engineering psychology to the area of Formal Engineering Methods, concentrating on validating the requirement specification at system analysis phase of a system development process. This paper presents a systematic approach to integrating specification animation into the process of writing requirements specification. The informal specification animation is used to enhance comprehensible interactions in obtaining feedbacks from the user for the purpose of specification validation, which also improve the current specification. A case study for a travel agent system is used to proof the practicality of the proposed approach. An empirical experiment on the approach is also presented to demonstrate the effectiveness of the approach.